Cultural Challenges and Subtitling Strategies in American Animated Movies - Rababah, Luqman M; Al-Zoubi, Dania Nawaf (Journal of Posthumanism, 2025)
This article explores the cultural challenges in subtitling American animated movies, using the movie “Shrek” as a case study. The study aims to identify the cultural challenges that subtitlers may encounter while subtitling American animated movies and exploring the strategies employed in subtitling American animated movies. Using the qualitative approach and Fernandez Guerra's (2012) classification of translation strategies, the researcher analyzed twelve examples taken from the movie series "Shrek". The findings of the current thesis show that subtitling American animated movies into Arabic requires a thorough understanding of both cultures ; it also emphasizes the importance of bridging cultural gaps in order to communicate effectively with Arabic-speaking audience. The findings of the study also showed that subtitlers face diverse cultural challenges, including idiomatic expressions and proper names. Such challenges require a nuanced understanding of both source and target cultures, as their task is not just linguistic but also involves a nuanced balancing act.